A contribution to the determination of the frequency discrimination ability - KALUŽNÝ, J.; MAJERNÍK, V.; KALUŽNÁ, M. (Archives of Acoustics, 1985)
The DL's for frequency as a function of the interstimulus intervals are experimentally determined. It is shown that the difference limens for frequency for both non-stationary and stationary signals clearly depend on the duration of the interstimulus interval up to the value N 256 ins. Moreover, it is shown that the recently published values of difference limen for frequency can be analytically expressed as the product of an exponential function and a resonance one where frequency and signal duration are parameters.